EFEKTIVITAS LEADER TOKO DALAM PROSES PROMOSI JABATAN KARYAWAN: STUDI KASUS DI PT INDOMARCO PRISMATAMA CABANG PARUNG, KABUPATEN BOGOR - Meilita Lestari; Laila Listiani Putri (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
Abstract. This research aims to describe the effectiveness of store leaders in the job promotion process at PT Indomarco Prismatama, Parung Branch, Bogor Regency. The study addresses the gap between the company’s merit-based promotion policy and its actual implementation at the store level. This study employs a qualitative method using case study approach. Data were collected through semi-structured interviews with four key informants: Chief of Store, Store Senior Leader, HRD Manager, and Store Crew supported by non-participatory observations and documentation studies. Data analysis was conducted using systematic thematic analysis in six stages, from transcription and coding to the development of a conceptual model. The findings reveal four dominant themes: (1) passive leadership and limited communication, reflected in irregular briefings and minimal feedback; (2) discrepancy between policy and practice, where performance-based criteria are not fully implemented; (3) perception of favoritism and low transparency, leading to doubts about objectivity; and (4) the store leader’s role in pre-promotion coaching, which remains selective and uneven among employees. The study concludes that leadership effectiveness plays a crucial role in bridging HRD policy and field implementation. Communicative, empathetic, and consistent leadership enhances transparency and employee motivation, while passive leadership weakens trust in the promotion system and hinders merit-based career growth.